Medical Image Watermarking Scheme Using 13 Bits Enhanced Block Average Intensity - Tan Gui, Jiu (2013)
This research is proposed the watermarking scheme in tamper localization which is able to detect the location of the manipulated areas and verify the authentic by using the block average intensity. The watermark data for ROI will store in the region of RONI. The embedded watermark allows the image have been tamper can recover and check for the tampering detection. The usage of the block average intensity is one of the popular techniques due to its easy to implementation. In this research, the tamper localization will performed using block average intensity in the tamper watermarking scheme for medical image. The block average intensity and the sub-block average intensity will be used to find out the tamper area by using the authentication bit, parity check bit and average authentication bit.